Predicting Residual Rectal Adenocarcinoma in the Surgical Specimen after Preoperative Brachytherapy with Endoscopic Ultrasound - Joseph Romagnuolo; Josée Parent; Té Vuong; Mélanie Bélanger; René P Michel; Paul J Belliveau; Judith L Trudel (Canadian Journal of Gastroenterology, 2004)
BACKGROUND AND STUDY AIMS: A novel brachytherapy (BT) protocol evaluated at McGill University has shown promise in terms of downstaging and achieving high tumour sterilization rates in rectal cancer. Endoscopic ultrasound (EUS) has emerged as the imaging modality of choice for local staging of rectal cancer. However, external beam radiotherapy appears to decrease the accuracy of EUS from 85% to 40%. The aim of the present study was to prospectively evaluate the accuracy of EUS in assessing the response of rectal cancer to BT.